Photoluminescence and Characterization of Eu2+ Doped Ca10(PO4)6F2 phosphor - Panse, Vishal R; Saregar, Antomi; Dewalkar, Snehal V; Waghare, S. M.; Dixit, Aparna (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
Efficient blue-emitting phosphors are crucial for the development of near-ultraviolet (near-UV) pumped white light-emitting diode (LED) devices. In this study, Ca10(PO4)6F2 triggered with Eu2+ phosphors were successfully synthesized via a facile combustion synthesis route in an open-air environment, enabling the formation of homogeneous and crystalline fine powders. The structural and morphological characteristics were analyzed using X-ray diffraction (XRD) and scanning electron microscopy (SEM), confirming the formation of a single-phase apatite structure with well-defined particle morphology. Photoluminescence (PL) properties were investigated under ultraviolet excitation. The synthesized Ca10(PO4)6F2:Eu2+ phosphors exhibited an intense blue emission centered at 432 nm when excited at 348 nm, which is attributed to the allowed 4f7  4f65d1 electronic transition of Eu2+ ions. The strong blue emission in the near-UV excitation region indicates effective luminescence performance of the host lattice. These results demonstrate that Ca10(PO4)6F2:Eu2+ phosphors prepared by the combustion method are promising candidates for blue-emitting components in near-UV pumped white LED applications.